Religion and consumer behaviour in developing nations: a look into the future - Fourali, Chahid; Gbadamosi, Ayantunji (Edward Elgar Publishing, 2021)
This is a conceptual chapter which sets out to critically review and integrate the themes covered throughout this book but also develop its own arguments about the urgency for marketers to advance their understanding and tools that help them identify religious needs in order to serve them profitably. In this process, the chapter reviews the link between ethics and business vis-à-vis the religious factor in the context of broader consumer behaviours, and critically determines the way forward. Specifically, the chapter undertakes the following: